GERM-15. A PHASE 2 TRIAL OF RESPONSE-BASED RADIATION THERAPY FOR PATIENTS WITH LOCALIZED CENTRAL NERVOUS SYSTEM GERM CELL TUMORS (CNS GCT): A CHILDREN'S ONCOLOGY GROUP (COG) STUDY. Issue 2 (22nd June 2018) - Fangusaro, Jason; Wu, Shengjie; MacDonald, Shannon; Murphy, Erin; Shaw, Dennis; Bartels, Ute; Khatua, Soumen; Boyett, James; Williams-Hughes, Chris; Souweidane, Mark; Lu, Hsiao-Ming; Morris, David; et al.
Abstract: Intracranial germ cell tumors represent 3-5% of pediatric CNS tumors. Non-germinomatous germ cell tumors (NGGCT) have worse outcomes compared to germinomas, however, improved survivals were achieved on COG ACNS0122 utilizing a combination of chemotherapy and craniospinal irradiation (CSI). Since CSI is associated with significant late effects, a Phase 2 study was undertaken to determine whether irradiation could be reduced without impacting survival in a subgroup of NGGCT patients. Patients with localized disease who achieved a complete (CR) or partial response (PR) to chemotherapy were eligible for reduced irradiation to 30.6Gy whole ventricular field (WVI) and 54Gy tumor-bed boost as compared to 36Gy CSI plus tumor-bed boost as used on ACNS0122. Between 5/2012 and 11/2016, 107 eligible patients were accrued. Median age was 11 years (range: 4-22) and 75% were male. Tumor location was pineal in 58, suprasellar in 37, ventricular in 6 and bifocal in 6 patients. Sixty-six patients achieved CR/PR post-induction and received reduced irradiation. The 2-year progression-free survival (PFS) was 89% (95% CI: 81%-97%) and overall survival was 92% (95% CI: 86%- 99%). Eight patients progressed; seven had a distant relapse (outside the irradiation field) and one patient had a local plus distant relapse. Alpha-fetoprotein and beta-human chorionic gonadotropin levels were not associated with PFS. There were no unexpected treatment-related adverse events or deaths. Although these survival data are encouraging, distant relapses noted in all of the patients who progressed are concerning. Longer follow-up of the ACNS1123 cohort may better inform our recommendations in the future.